Anthropophagy: An Update In Context Of Oral Pathologies - Dr. Harish Kumar, Dr. Roquaiya Nishat, Dr. Anupama Desai (International Journal of Advanced Science and Technology, 2020)
Cellular cannibalism has been defined as the ability of a cell to engulf another living cell leading eventually resulting in death of the internalized cell. This mechanism exhibited by tumor cells can be instrumental in either their survival or proliferation. Presence of these cells can act as a promising entity to determine the aggressiveness and hence the prognosis of a lesion. This review provides an insight into cellular cannibalism, types, mechanism and pathogenesis, other cell in cell phenomena and also a gist of studies done in this field in oral lesions.